Explosive spalling of ultra-high performance concrete at high temperature - Ngo, Pit Soon (2017)
In the past two centuries, concrete has made a remarkable impact on human history. Nowadays, Ultra-high performance concrete (UHPC) is increasingly used as a construction material in the building industry due to its physical properties such as excellent durability, strength and constructability. However, most UHPCs are at risk of explosive spalling in fire, which may result in the loss of concrete cover and substantial cross section, exposing steel reinforcements to fire and reducing load-bearing capacity of structures. The consequences of fire attack on these concretes are not limited to damages on structural components but also on the safety of occupants. The objectives of this research are to develop a relationship between the mechanical properties of UHPC with the addition of Steel (ST) and Polypropylene (PP) fibres. Besides that, mechanism of the synergistic effect of PP and ST fibres on spalling will be discussed. Lastly, effect of permeability and tensile strength on the spalling behaviour will be analysed to identify the relationship of these two parameters. In total, 16 mixes were used to evaluate the above parameters on the performance of UHPC with varying amounts of ST and PP fibres. Four types of tests were conducted to obtain the properties of the concrete mix, i.e. Uniaxial Tensile Strength Test, Compressive Strength Test, Permeability Test and Explosive Spalling Test. Scanning Electron Microscope (SEM) analysis was used to understand the behaviour of the ST and PP fibres at micro-structure level of concrete. Based on experiments conducted, the results proved that sole addition of ST fibres does not have much impact on prevention of spalling of concrete. However, when replacing ST fibres with PP fibres, the spalling resistance improves. Furthermore, upon addition of both PP and ST fibres, the spalling prevention effect is the best as compared to adding only one type of fibres. Future works are planned and reported in Chapter 5. Recommendations for further research are discussed.